ANALYSIS OF AIRFOIL USING WIND TUNNEL THROUGH IMAGE PROCESSING - Abdul Sami; Arish Khan; M. Uzair Taqi; Syed Najeeb Haider Jafri (Spectrum of Engineering Sciences, 2025)
This project introduces a novel approach to measuring aerodynamic parameters using digital image processing, offering a simpler and more cost-effective alternative to traditional wind tunnel methods involving manometers and anemometers. The study explores three main methodologies, including Computational Fluid Dynamics (CFD), pressure sensors, and image processing, with a focus on the latter. By recording airflow behavior over an airfoil using a high-quality digital camera and analyzing the footage in MATLAB, pressure and velocity were determined effectively. A smoke generator was used to visualize airflow patterns in the wind tunnel. The image processing results showed strong agreement with anemometer readings and CFD simulations, confirming its reliability. This method simplifies aerodynamic testing and offers a more efficient alternative to conventional techniques.